2017
DOI: 10.1515/aopf-2017-0020
|View full text |Cite
|
Sign up to set email alerts
|

Phytoplankton response to fish-induced environmental changes in a temperate shallow pond-type lake

Abstract: Since 1967, the temperate, shallow, pond-type Lake Warniak has been subjected to different biomanipulation methods including the introduction of common carp,Cyprinus carpioL., grass carp,Ctenopharyngodon idella(Val.), silver carp,Hypophthalmichthys molitrix(Val.), and bighead carp,Hypophthalmichthys nobilis(Richardson) and then their removal in an effort to control macrophytes and phytoplankton. Recently, pilot stocking with predatory fish, particularly pike,Esox luciusL., has also been conducted. Hence, an ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 22 publications
(38 reference statements)
0
10
0
Order By: Relevance
“…Furthermore, global warming, elevated trophic state, and decreased density of large-sized grazers [73] exert a strong influence on cyanobacteria-dominated phytoplankton. A general trend of a successive increase in the average annual air temperature in the same region [74] as the studied lake showed that the average annual temperature, after 2000 compared to the 46-year (1953-1999) mean temperature, was always higher and the annual deviations have reached to 2.2 • C up to date. In our study, the average water temperature was 21.2 • C and 14.0 • C in July and October 2016, respectively, and 7.8 • C, 18.2 • C and 6.6 • C in March, July and November 2017, respectively.…”
Section: Discussionmentioning
confidence: 65%
“…Furthermore, global warming, elevated trophic state, and decreased density of large-sized grazers [73] exert a strong influence on cyanobacteria-dominated phytoplankton. A general trend of a successive increase in the average annual air temperature in the same region [74] as the studied lake showed that the average annual temperature, after 2000 compared to the 46-year (1953-1999) mean temperature, was always higher and the annual deviations have reached to 2.2 • C up to date. In our study, the average water temperature was 21.2 • C and 14.0 • C in July and October 2016, respectively, and 7.8 • C, 18.2 • C and 6.6 • C in March, July and November 2017, respectively.…”
Section: Discussionmentioning
confidence: 65%
“…Ammonium-nitrogen was at the same level in both periods, especially at the selected sites of the Tushka and Abu Simble regions. Similarly, the higher phytoplankton density and total coliform bacteria but lower zooplankton density were found at these sites (i.e., sites [10][11][12][13][14][15]. The comprehensive study of environment of Lake Nasser before operating the Renaissance Dam indicated regional variations in all of the parameters.…”
Section: Discussionmentioning
confidence: 84%
“…Phytoplankton and zooplankton have become good indicators commonly used for monitoring the environmental conditions [7], and they quickly respond to any changes in the water quality [8,9]. Both phytoplankton and zooplankton are, thus, of great importance in the ecological and economic context due to their roles in aquatic food networks and, consequently, in fishery management [10,11]. Furthermore, aquatic organisms provide many ecological benefits and are essential in promoting the diversity and function of aquatic systems [12].…”
Section: Introductionmentioning
confidence: 99%
“…Trophic efficiency (TE) was used to describe the relations between zooplankton and phytoplankton, and the total zooplankton biomass to total phytoplankton biomass ratio was calculated. The classification of the efficiency level followed the class thresholds given in Napiórkowska-Krzebietke [ 52 ], i.e., from the lowest to the highest—maximum of: 0.20 for class I, 0.40 for class II, 0.60 for class III, 0.80 for class IV, and 1.00 for class V.…”
Section: Methodsmentioning
confidence: 99%